2006
DOI: 10.1088/0953-8984/18/40/011
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence responses from europium doped gadolinium oxide

Abstract: Thermoluminescence signals and morphological studies are reported for a new phosphor of Gd2O3. The phosphor particle material was synthesized by an aerosol technique and it is heavily doped with Eu. Annealing at 1200 °C increases the luminescence efficiency by ∼1000-fold relative to the as-prepared material. The emission spectra are primarily from the red transitions of the Eu, but weaker short wavelength emissions can also be detected during low temperature thermoluminescence. There are numerous wavelength de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…This glow peak has simple structure and trap distribution which might be used in radiation dosimetry above 60 Gy g-irradiation. Wang et al [40] have studied the TL responses from Eu doped X-rays. They observed six glow peaks at $ 48, 77, 98, 125, 137, 198 and 280 1C, respectively.…”
Section: Thermoluminescence (Tl) Studiesmentioning
confidence: 99%
“…This glow peak has simple structure and trap distribution which might be used in radiation dosimetry above 60 Gy g-irradiation. Wang et al [40] have studied the TL responses from Eu doped X-rays. They observed six glow peaks at $ 48, 77, 98, 125, 137, 198 and 280 1C, respectively.…”
Section: Thermoluminescence (Tl) Studiesmentioning
confidence: 99%
“…Gadolinium or Yttrium doped with Europium oxides are important due to their luminescent properties [15,16]. Higher luminescence efficiency and long-term stability of this material are mostly associated with investigating optimum doping concentration, nanostructuring and obtaining overall morphology control.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescence studies carried out in Gd 2-O 3 :Eu 3+ phosphor system have demonstrated that annealing and crystalline phases control both the thermoluminescence and radioluminescence signals [15]. Characteristic bands in the emission spectra are assigned to Eu 3+ ion radiative 5 D 0 ?…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] SP involves extreme synthesis conditions occurring at the level of a micrometer-sized aerosol droplet in a disperse system, thus enabling the synthesis of metastable structures, as previously reported. [21,22] There are certain process parameters, such as high heating and cooling rates, short residence times, and an additional thermal treatment, which may affect the yield of either thermodynamically (YAG, YAM) or kinetically (YAP) stable phases.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] SP involves extreme synthesis conditions occurring at the level of a micrometer-sized aerosol droplet in a disperse system, thus enabling the synthesis of metastable structures, as previously reported. [21,22] There are certain process parameters, such as high heating and cooling rates, short residence times, and an additional thermal treatment, which may affect the yield of either thermodynamically (YAG, YAM) or kinetically (YAP) stable phases. [12] The introduction of organic components into the solution is becoming increasingly popular, since these components provide the retention of the proper stoichiometry during the process, and the reaction that occurs in the solution leads to volume precipitation and the formation of dense particles.…”
Section: Introductionmentioning
confidence: 99%